Clinical profiles and outcomes of neonates with neonatal hyperbilirubinemia and treated with double volume exchange transfusion: a retrospective study - Pradhan, Janaki Ballav; Kamalarathnam, C. N. (International Journal of Contemporary Pediatrics, 2019)
Background: Double volume exchange transfusion (DVET) for severe unconjugated hyperbilirubinemia has become less common events now days in pediatric practices. But kernicterus is still common in low income country like India. The aim of the study was to determine the clinical profile and outcome in neonates who were treated with DVET. Methods: This was a retrospective study in neonate’s ≥34 weeks of gestation that were treated with DVET for severe neonatal hyperbilirubinemia over a period of four years. Results: In our study, 37 neonates underwent DVET. Male neonates (62.13%) and normal vaginal delivery (NVD) (70.2%) are common. ABO Isoimmunisation was commonest cause (56.75%) of exchange transfusion. The mean TSBR at pre exchange and Post Exchange were 27.39 ± 5.99mg/dl and 15.16 ± 4.00mg/dl (p<0.05). Ten neonates (27%) among 37 neonates required twice DVET.Thrombocytopenia14 (37.83%); Seizure 5(13.5%) and Hypocalcaemia 3(8.1%) were common complication noted among total 17 (45.94%) neonates. BIND occurred in 15 neonates (40.5%) at the time of admission and seven (18.9%) neonates had persistent neurological abnormality at discharge. Neonate with BIND had early onset of jaundice (44.13±15.37 hours vs. 61.22±28.23hrs, p<0.05), with higher pre exchange TSBR value(28.96 ±8.5mg/dl vs. 26.22±3.17mg/dl). Neonates admitted with BIND had higher percentage of persistent encephalopathy (40% vs. 4.5%,p<0.05), abnormal tone (33.3% vs. 4.5%,p<0.05), abnormal feeding (33.3% vs. 4.5%,p<0.05) and abnormal posture (26.6% vs. 0%,p<0.05) at discharge as compared to those without BIND. No death occurred in this study population. Conclusions: Early detection and aggressive therapy with DVET can prevent neonates from brain injury.